KONTRIBUSI DAN PELUANG PENINGKATAN PENDAPATAN ISTERI NELAYAN TERHADAP PENDAPATAN KELUARGA DI KECAMATAN ALUH-ALUH KABUPATEN BANJAR KALIMANTAN SELATAN - Ulfah Nurul Hidayah; Idiannor Mahyudin; Emmy Sri Mahreda (Faculty of Fisheries and Marine Resources of Lambung Mangkurat University-South Kalimantan, 2019)
Purpose of this study is identify the types of work fisherman’s wife in Subdistrict Aluh-aluh, analyzing the contribution of revenue fisherman’s wife to family income and Analyzing the fisherman’s wife increased revenue opportunities to family income.The research method used a descriptive method and survey method. Data collection performed with observation and interview techniques. Technique of sampling locations use purposive sampling and respondents sampling use purposive randomsampling.The results showed that types of work fisherman’s wife performed in fisheriesinclude : salted fish processing, shrimp paste processing, processing ebi, ang processing of prawn crackers, revenue contribution fisherman’s wife who worked as a salted fish processing amounted to 32,32%, as processing shirmp paste amounted to 31,29%, asprocessing ebi amounted to 31,01%, as processing shrimp crackers amounted to 23,95%.Average revenue contribution amounting to 29,64%, fish crackers opportunies amountedto 48,58%, shrimp meatball amounted to 30,36%, shrimp amplangs amounted to 10,12%,and shrimp nuggets amounted to 10,93%.